Artificial Intelligence (AI) for Automated Writing Evaluation in TESOL: Effectiveness and Challenges - Jannath, Husnul; Akter, Antura (JOLLT Journal of Languages and Language Teaching, 2026)
Artificial Intelligence (AI) is having a significant influence on language learning, primarily through Automated Writing Evaluation (AWE), which gives quick and personalized feedback to learners. However, there is not enough research on the effectiveness and challenges in establishing higher-order writing abilities in the TESOL context. This study reviews the available research on how AI-based AWE supports TESOL writing and what problems it might have. This research follows Braun and Clarke's (2006) thematic analysis of 55 peer-reviewed studies from academic sources (e.g., Scopus, Google Scholar, JSTORE, ERIC) published between 2018 and 2025 reporting findings on the effect of AWE on pedagogy in TESOL teaching. The findings focus on both the effectiveness and the challenges of AWE tools. The analysis highlights themes such as improved linguistic accuracy, enhanced learner motivation, and personalized learning experiences, which contrast with challenges like academic dishonesty, ethical concerns, over-reliance on AI, and limitations in addressing higher-order cognitive skills. These findings indicate that while AWE tools significantly improve grammar, vocabulary, and writing fluency, these are less effective in developing critical thinking and argumentation. The study suggests the need for blended feedback models that combine AI feedback and teacher guidance, the implementation of ethical guidelines, and the conduct of long-term research to see how AWE affects advanced writing skills over time.